Etterforskning av illegal ulvejakt - Paul Larsson (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article deals with the investigation of illegal wolf hunting. It analyses methods and procedures of investigation based on a sample of cases and interviews. The police are often criticised when dealing with wolf cases, as this is a field dominated by strong emotions. Police are either denounced for using too many resources or criticised for not treating illegal hunting as seriously as they should. These cases are demanding to investigate. Single pieces of evidence rarely determine the outcome of the investigation. What matters is the totality of the evidence. Investigations vary by type of case. Most cases fall into one of three categories: those in which the police initiate and “build” the case proactively; those in which a hunter is “caught in the act”; and those in which the shooter reports the incident to police him or herself – generally describing it as an act of selfdefence.